An Analysis of Online Classroom Management for English Subject at Sekolah Harapan Utama, Batam - Pandu Prasodjo; Sabarina Moksin; Desty Febria (English Language in Focus (ELIF), 2022)
Due to this pandemic, the teacher needs to design a proper strategies suit to stu-dents learning condition. While trying to adjust with the changing, the teacher still has to maintain the teaching learning effectiveness. However, teachers had to use technological tools and improve the student’s interest in learning English subject. This research aim is to analyze or to identify how the English teacher engage the students by having an observation sheet in collecting the data. The study used qualitative research method. The subject of this study was the teacher strategies in online teaching and the uses of technological tools for SMP grade 9 at SHU. The result shows that, the use of technological tools improve the students learning pro-cess for English subject. But teachers’ strategies were not effective because teach-ers speak full English but some of them find it hard to engaged in. This research focuses on the teachers’ strategies in teaching and using the technology as for the English teaching. However, with the use of technology during teaching and learn-ing process, researcher concluded that there is improvement for the students in learning the English subject and possibly attract the students’ interest while learn-ing English subject virtually.